2003
DOI: 10.1136/bjo.87.5.570
|View full text |Cite
|
Sign up to set email alerts
|

Patchy atrophy and lacquer cracks predispose to the development of choroidal neovascularisation in pathological myopia

Abstract: Aims: To determine the incidence and predisposing findings for choroidal neovascularisation (CNV) in a large series of highly myopic patients. Methods: The medical records of 218 consecutive patients (325 eyes) with myopic fundus changes in the macula were reviewed. The incidence of CNV during a follow up of at least 3 years of highly myopic patients and identification of predisposing findings for the development of myopic CNV were examined. Results: Among 325 highly myopic eyes examined, 33 eyes (10.2%) devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
202
2
12

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(222 citation statements)
references
References 13 publications
4
202
2
12
Order By: Relevance
“…Nearly 10% of eyes with degenerative retinal findings consistent with high myopia develop CNV. 11 The precise pathogenesis of myopic CNV remains unclear. However, some authors have suggested that mechanical tissue strain caused by stretching may lead to the development of choroidal ischaemia, followed by atrophy of both the RPE and the overlying retina, and the subsequent release of growth factors.…”
Section: Pathological Myopiamentioning
confidence: 99%
“…Nearly 10% of eyes with degenerative retinal findings consistent with high myopia develop CNV. 11 The precise pathogenesis of myopic CNV remains unclear. However, some authors have suggested that mechanical tissue strain caused by stretching may lead to the development of choroidal ischaemia, followed by atrophy of both the RPE and the overlying retina, and the subsequent release of growth factors.…”
Section: Pathological Myopiamentioning
confidence: 99%
“…5 % hochmyoper Augen gefunden [27]. In einer prospektiven Erfassung über 10 Jahre entwickelten 10 % eine neue myope CNV (mCNV) [112]. [140].…”
Section: Zentrale Netzhaut Und Myope Choroidale Neovaskularisationunclassified
“…This may be because ageing, in addition to mechanical stretching of the eyeball, might be important for the development of predisposing factors such as RPE atrophy and lacquer cracks. 47 However, myopic CNV has been reported in children. [48][49][50] In our study, of the two patients with myopic CNV, one had coexisting osteogenesis imperfecta.…”
Section: Choroidal Neovascularization In Children and Adolescents P Rmentioning
confidence: 99%